An Improved Model for Evaluating the Brittleness of Shale Oil Reservoirs Based on Dynamic Elastic Properties: A Case Study of Lucaogou Formation, Jimusar Sag. (4th May 2022) - Gao, Yang; Dong, Yan; Chen, Lei; Li, Yingyan; Qin, Jianhua; Jiang, Zhenxue
Abstract : Rock brittleness is a critical factor affecting the stimulation of shale oil reservoirs. For efficient development of the shale oil in Lucaogou Formation, Jimusar Sag, the brittleness of the sweet spots needs to be evaluated. In this paper, the triaxial compression, acoustic wave measurements, and three-point bending tests were carried out on the reservoir cores. Based on the prepeak energy characteristics of the stress-strain curve, the brittleness of different horizons was calculated, with the largest difference of 24.89%. An improved model based on dynamic elastic properties was proposed to evaluate the brittleness along the vertical pay zones, by which the continuous brittleness in the upper sweet spot was found more changeful than that in the lower sweet spot. The linear correlation coefficient between the brittleness from the improved model and that from the laboratory tests is 0.85, improving the accuracy by 21% and 27% respectively, compared with the conventional elastic property methods. From the characteristics of compression fractures and the length of the fracture process zone, it was found that the compression fractures were more complex and the fracture process zone length was shorter in a more brittle rock, verifying the reliability of the improvement model. The improved method based on dynamic elastic properties proposed in this paper is expected to guide the brittleness evaluation in other regions.